Elevating Network Security: A Novel S-Box Algorithm for Robust Data Encryption - Alqahtani, Jarallah; Akram, Muhammad; Ali, Ghassan Ahmed; Iqbal, Nadeem; Alqahtani, Ali; Alroobaea, Roobaea (IEEE access, 2024)
In an era characterized by ever-increasing data exchange across different networks, the importance of robust network security measures cannot be overemphasized. Cryptographic algorithms, on the other hand, perform a vital role in imparting security to the sensitive information during transmission, with S-Boxes (Substitution Boxes) serving as a fundamental component of symmetric-key ciphers. This study has endeavored to engineer a novel S-Box algorithm to bolster the network security. Moreover, the core focus of the suggested algorithm lies in enhancing the confidentiality, defiance to nefarious designs of cryptanalysis savvy, and overall cryptographic strength of data encryption in network communication. Random numbers spawned by the 5D multi-wing hyperchaotic system have been employed to design the proposed box. Apart from that, Rook -a chess piece has been used in this regard. Particularly, the random walk of Rook on the 16 × 16 hypothetical chessboard has been capitalized to sufficiently permute the data of the potential S-Box. Through a comprehensive performance evaluation and cryptographic analyses, the proposed S-Box algorithm exhibits superior resilience against diverse threats thus fortifying network security effectively. In particular, the state of the art security parameters like bijectivity, non-linearity (NL), strict-avalanche criterion (SAC), bit-independence criterion (BIC), linear probability (LP) and differential probability (DP) have been used. This work, no doubt, contributes significantly to the ever-evolving field of network security.